IEEE Conference on Decision and Control and European Control Conference 2011
DOI: 10.1109/cdc.2011.6160453
|View full text |Cite
|
Sign up to set email alerts
|

Observer design on the Special Euclidean group SE(3)

Abstract: Abstract-This paper proposes a nonlinear pose observer designed directly on the Lie group structure of the Special Euclidean group SE(3). We use a gradient-based observer design approach and ensure that the derived observer innovation can be implemented from position measurements. We prove local exponential stability of the error and instability of the non-zero critical points. Simulations indicate that the observer is indeed almost globally stable as would be expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 10 publications
0
63
0
Order By: Relevance
“…In several robotics applications where the considered Lie group is SO(3) and where the outputs live in copies of S 2 , as well as in the case where the considered Lie group is SE(3) and the homogeneous output spaces are copies of R 3 , it has been shown that the reductivity condition imposed by part (d) of Proposition 4 holds and hence the resulting observer is implementable based on sensor measurements [15], [11].…”
Section: Constructing a Cost Function On The Lie Groupmentioning
confidence: 99%
See 1 more Smart Citation
“…In several robotics applications where the considered Lie group is SO(3) and where the outputs live in copies of S 2 , as well as in the case where the considered Lie group is SE(3) and the homogeneous output spaces are copies of R 3 , it has been shown that the reductivity condition imposed by part (d) of Proposition 4 holds and hence the resulting observer is implementable based on sensor measurements [15], [11].…”
Section: Constructing a Cost Function On The Lie Groupmentioning
confidence: 99%
“…Specifically, when the output manifold is a reductive homogeneous space of the Lie group, the authors in [14], [15] propose an observer design on the output manifold and then lift the designed observer to obtain a corresponding observer on the Lie group. The approach can be applied to many interesting real world scenarios such as attitude estimator design on the Lie group SO (3) or pose estimation on the Lie group SE(3) [3], [7], [11], [18], [20], [26]. For the specific cases of attitude estimation on SO(3) and pose estimation on SE(3), some methods have been proposed for the concurrent estimation of an unknown constant bias corrupting the velocity measurement [18], [26], [27].…”
Section: Introductionmentioning
confidence: 99%
“…An example is shown by Vasconcelos et al [15] in which estimation is done by using known landmarks. Similar work is done by Hua [16] and Bras et al [17], where the latter is for range-only measurements. These methods require prior knowledge of the landmarks position which makes them fall short on the SLAM problem.…”
Section: Introductionmentioning
confidence: 62%
“…In simulations the observer has been tested with initializationθ li = π without any convergence problem. The bias estimated can then be used in cascade with the simplified complimentary filter from [16] …”
Section: E Slam Attitude Problem Formulationmentioning
confidence: 99%
“…In [10] an exponentially convergent nonlinear observer on SE(3) was presented with almost global stability for attitude, position and bias estimation, using landmark measurements and non-ideal velocity readings. A gradient-based observer on SE(3) using position measurements, was designed in [11], however, the effect of bias was not considered. In [12], using strapdown inertial measurements, GPS, and vector observations, discrete-time complementary filters for estimating the attitude and position with compensating for rate gyro bias was proposed.…”
Section: Introductionmentioning
confidence: 99%